(untitled) (Scientific journal of the Fergana State University, 2023)
This article examines the role of Abu Nasr Farabi in world science and the importance of his legacy today. Also, in the article, the focus on science in the philosophical views of the thinker, the classification of different sciences is explained. Also, the opinions of scientists regarding his contribution to the field of science were analyzed